Statin use and risk of cancer: An umbrella meta-analysis - Ruby Kasana; Christy Thomas; Gaurav Das; Munlima Hazarika; Krishna Undela (Annals of Oncology Research and Therapy, 2023)
BACKGROUND: The relationship between statin use and cancer risk has been debated for a long time. Physiologically plausible theories suggest that statins may lower the risk of cancer. We have updated the overview of meta-analyses to include up-to-date information, additional subgroup analyses, and site-specific cancer risk estimates. MATERIALS AND METHODS: A systematic search was performed in the PubMed, Cochrane and Google scholar databases between June 2016 and December 2022. The search strategy included both statin- and cancer-related keywords. Meta-analyses examining the association between statin use and site-specific cancer risk were included. Two reviewers independently screened the literature, extracted data, and assessed the study quality using A MeaSurement Tool to Assess systematic Reviews 2 (AMSTAR 2) tool. RESULTS: This up-to-date overview included 71 meta-analyses (33 new and 38 from the previous overview) of 14 site-specific cancers. Out of which, 29 (44%) meta-analyses had a “Critically low” and three reviews (5%) had a “High” quality of evidence with AMSTAR 2. The pooled results of meta-analyses showed that statins reduce the likelihood of biliary tract (33%), colorectal (9%), gastric (29%), gynecological (12%), hematological (19%), liver (42%), esophageal (19%), and pancreatic (18%) cancers. However, no association was identified between statin use and the risk of bladder, breast, kidney, lung, prostate, and skin cancers. CONCLUSIONS: Statins may play a crucial role in cancer chemoprevention, reduce the risk of site-specific malignancies, and can be used as an adjuvant.